Localized Myxedema on the Upper Eyelids in a Patient of Hypothyroidism - Hidetoshi Takahashi; Akemi Ishida-Yamamoto; Hajime Iizuka (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2016)
A 42-year-old Japanese woman presented with upper eyelid swelling of 2 months duration (Figure 1a). She did not complain muscle weakness or myalgia. She showed no dry coarse skin, tremors of the hands, thick tongue, or loss of hair. Histopathology of the skin biopsy revealed swelling of the collagen bundles with splitted individual fibers accompanied with pale material (Figure 1b), which was stained with blue with colloidal iron (Figure 1c).Laboratory investigation revealed decreased free T4 (0.88 ng/ml(1-1.8)), decreased free T3 (1.12 pg/ml (2.73-4.5)), and increased TSH (10.34 IU/ml (0.27-4.29). Anti-thyroid, anti-microsome, antithyrogloblin and anti-thyroid peroxidase antibodies were positive.Total cholesterol (286 mg/dl) and triglyceride (342 mg/dl) were elevated. Other laboratory findings including anti-nuclear antibody, aldolase, creatine kinase, and angiotensin-converting enzyme showed normal results. Echo examination disclosed slight but diffuse swelling of thyroid gland. Chest X-rays showed no abnormality and no malignant disease was detected in CT. The patient was diagnosed as localized myxedema with hypothyroidism due to Hashimoto disease.After three months of thyroid hormone replacement therapy, the skin lesions gradually improved accompanied with euthyrodic state. We got the informed consent form the patient.